The Edge is not How You Paint It. The Case of the Southern Edge of Bogota, D. C. - Garavito G., Leonardo; De Urbina G., Amparo (Universidad del Rosario, 2019)
This paper presents some reflections and advances derived from an ongoing research project called “Territories of water and networks of practice and learning for the appropriation of knowledge and collaborative management in the southern edge of the Capital District”. It focuses on problematizing and evidencing the underlying polysemy after the idea of the border applied to the city of Bogota, and especially to its southern territories. In this sense, it is argued that there are many and different edges interacting and overlapping each other, aiming at building a more complex and comprehensive view of the territory on the southern edge of the Capital District. The methodology is based on the revision of secondary sources, complemented with interviews with key informants.